The Improving Narrative Text Writing Skills by Using the Fractured Story In Class X Students of SMAN 1 Pademawu - Ulfah; Rohit Alfarisi; Jaftiyatur Rohaniyah; Maretha Kaltasia (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2025)
This Classroom Action Research aimed to improve the narrative writing skills of tenth-grade students at SMAN 1 Pademawu through the implementation of the Fractured Story model. The study involved 28 students and was conducted over two cycles following the stages of planning, action, observation, and reflection. Data were collected using pretests, posttests, observations, and documentation. In the pretest, none of the students achieved the minimum passing score of 75, with an average score of only 45.00. After the first cycle, the average score increased to 69.11, with 28.57% of students reaching the minimum criteria. In the second cycle, all students passed, achieving an average score of 95.89. This shows a total improvement of 50.89 points or 113.09% from the pretest. The results indicate that the Fractured Story model effectively enhanced students’ writing performance, motivation, creativity, and critical thinking. By reconstructing well-known stories into new and imaginative narratives, students developed a better understanding of narrative structure and gained more confidence in expressing their ideas. The model also made learning more engaging and meaningful, as it encouraged students to connect the content with their own experiences and imagination. Therefore, it can be concluded that the Fractured Story model is an effective approach to improve students’ ability in writing narrative texts in English language learning.